Práticas pedagógicas reflexivas e metodologias ativas: possibilidades na escola pública municipal em São Luís - MA - Nunes, Mônica Maria Avelar de Carvalho (2019)
Teacher training has been a widely discussed in school institutions, since educator training is an essential factor for students' teaching and learning. Thus, this research aims to investigate the possibility of implementing or not the application of reflective pedagogical practices and teaching-learning methodologies in a municipal school in São Luís - MA. It started from a qualitative approach, through research - participant, bibliographic, documental analysis (research diary) and observations of the researcher as sources of information, to corroborate the impressions and capture the meaning of the participants' pedagogical actions and the meaning by they attributed to the situations experienced. 15 (Fifteen) interns participated in the research who built field diaries about the experience of 10 (ten) regencies that were treated and analyzed through content analysis proposed by Bardin (2011), using Iramuteq Software. Therefore, the main results indicated that the trainees consider the student as the main actor, but don´t reflect on their pedagogical practice, it did not register conflicts, questions, learning, reflections about yourself. Few interns who have matured their professional identity to a pedagogical practice consistent with contemporary theories of education in initial training. It still needs to deconstruct concepts from traditional education to 21st century education. It is believed that, for teachers to develop a reflexive posture in their daily lives, there is a great need for this conduct to be from its initial formation, in the first semesters, aiming at the development of actions that become reflexive before, during and after. From the analyzes made by the researcher, some points that emerged from this investigation are highlighted as a possible contribution to teacher education: there is a need for training to contextualize the internships; within the school there is no collective space for reflection on the practice, the need to invest more and better in the knowledge of the experience developed.